Specialist‐led diabetes registries and predictors of poor glycemic control in type 2 diabetes: Insights into the functionally refractory patient from the LMC Diabetes Registry database. (24th March 2015) - Aronson, Ronnie; Orzech, Naomi; Ye, Chenglin; Goldenberg, Ronald; Brown, Vivien
Abstract: Background: The aim of the present study was to explore features associated with glycemic control in type 2 diabetes (T2D) patients undergoing care by specialist clinics. Methods: Literature searches identified diabetes registries whose databases recorded outcomes of specialist care. The LMC Diabetes Registry database ( n  = 58 280; LMC) was queried to identify patients with T2D who had been seen in a defined 14‐month period. Logistic regression modeling was used to identify predictors of glycemic control in these patients. Poor glycemic control was defined as HbA1c ≥9.0% (75 mmol/mol) despite specialist care for ≥1 year. Results: Few published registry‐based studies have discussed glycemic control and outcomes of specialist care for T2D. Among 10 590 LMC patients with T2D, mean HbA1c was 7.6% (60 mmol/mol), with 38% of patients meeting the Canadian Diabetes Association target of ≤7.0% (53 mmol/mol). Overall, 15% showed poor glycemic control with persistent HbA1c ≥9.0% (75 mmol/mol); among insulin‐treated patients ( n  = 3856), 28% met this criterion. Patient characteristics independently associated with poor glycemic control included early age of onset, the number of diabetes education program visits, the number of oral therapies, and insulin use. Conclusions: Type 2 diabetes patients with poor glycemic control are found disproportionately in referral specialist care clinics. These functionally refractory patients demonstrate features that may assist in predicting their potential outcome, and may represent a group with specific barriers to care. Specialist patient registries, such as the LMC Diabetes Registry, may provide critical information regarding this cohort.